The Role of Compassion during the Shift to Online Teaching for Language Teacher Wellbeing - Mairitsch, Astrid; Babic, Sonja; Mercer, Sarah; Sulis, Giulia; Shin, Sun (Theory and Practice of Second Language Acquisition, 2023)
Research on compassion has received increasing attention over the past decades (Seppälä et al., 2017). However, empirical studies focusing on the role of compassion for teachers still remain sparse to date. This paper reports on a study designed to investigate the wellbeing of 21 language teachers across the globe during the first wave of the COVID-19 pandemic crisis. In particular, the study sought out to examine the ways in which compassion and self-compassion contributed to the wellbeing of language teachers during this time. Data were generated through in-depth, semi-structured individual online interviews and were analyzed from a Grounded Theory perspective (Charmaz, 2006). Findings revealed that acts of compassion in the workplace and in the private lives of the teachers played a crucial role in shaping our participants’ wellbeing during this time of crisis. Furthermore, self-compassion emerged as an important factor influencing the wellbeing of teachers during the pandemic crisis. Indeed, compassion and self-compassion served as core elements in their teaching and appeared to affect their relationships with their students, colleagues, and headteachers. In the absence of compassion, the stressful and challenging situation they were already experiencing was exacerbated. These findings imply the potential benefits of compassion and self-compassion training for teachers, administrators, and policymakers to support and promote wellbeing in the educational workplace.